Impact of specific fracture energy investigated in front of the crack tip of three-point bending specimen - J. Klon; J. Sobek; L. Malíková; S. Seitl (Fracture and Structural Integrity)
Presented study is focused on the analysis of the dependence of the specific fracture energy value on the assumed work of fracture in threepoint bending tests. Specimens of different sizes and relative notch lengths are assumed in this study, in order to take into account the size effect. The three-point bending test of cracked specimens is simulated numerically by means of commercial software based on the finite element method with implemented cohesive crack model. Three levels of the specific fracture energy are considered.